Knowledge transfer for innovativeness in family businesses - Letonja, Marina; Duh, Mojca; Ženko, Zdenka (Serbian Journal of Management, 2021)
Family businesses (FB) are important in the most of national economies. We explored whether successors’ innovativeness is positively associated with the transfer of the founders’ innovativeness through knowledge transfer and creation processes in a form of the internal transfer of founders’ tacit and experiential knowledge and skills and with the external transfer of knowledge, when potential successors attend educational programs, external training, or gain working experience in other companies. Our research reveals that when the actual forms of internal knowledge transfer are discussed, the positive correlations exist between innovativeness of successors and their early inclusion into FB, apprenticeship, inclusion of successors into meetings with business partners and strategic planning before they get involved in FB. Our survey partially confirmed that regarding external transfer of knowledge, working experiences of successors in other companies and participation in academic courses are positively associated with their innovativeness.
Keywords: family business; innovation; knowledge transfer; succession